Boundaries, Intersections, and the Parting of Ways in the Letter of James - Elkins, Kathleen Gallagher; Bolin, Thomas M. (2020)
The letter of James reveals long embedded anti-Semitic elements at work in the articulation of the distinction between Judaism and Christianity. However, careful examination of the text and the history of the early synagogue and church challenges us to rethink how (and whether) Judaism and Christianity have parted ways. James’s use of biblical traditions is not simply an embrace of torah piety or “works righteousness,” but rather a careful juxtaposition of wisdom and prophetic traditions aimed to call the letter’s first readers, and us, to move toward the margins of our ecclesial, academic, and wider communities.
Keywords: Letter of James; Jewish Law; Parting of the Ways; prophetic critique; Wisdom Literature